Serum neurofilament light is associated with future disease activity in clinically isolated syndrome and early Multiple Sclerosis only after non-optic neuritis onset - Klyscz, Philipp; Ruprecht, Klemens; Anderhalten, Lina Carlotta; Schmitz-Hübsch, Tanja; Kuhle, Jens; Usnich, Tatiana; Bellmann-Strobl, Judith; Paul, Friedemann; Schindler, Patrick; Asseyer, Susanna (European journal of neurology, 2025)
Background We compared the prognostic value of serum neurofilament light chain (sNFL) and glial fibrillary acidic protein (sGFAP) for clinical and radiologic disease activity among patients with clinically isolated syndrome or early multiple sclerosis (MS) with optic neuritis (pwON) and non-optic neuritis (pwNON) as the first manifestation. Methods Patients within 7 months (pwON and pwNON) from disease onset and patients with MS with a disease duration longer than 12 months (pwMS) as controls were included. sNFL and sGFAP were analyzed at baseline and at follow-ups using SIMOA technology. Linear mixed models and Cox regression analyses were applied. Results We included 165 samples of 86 patients (18 pwON, 46 pwNON, 21 pwMS). Median follow-up time was 80 months. Mean sNFL z scores were higher in pwNON (1.06) than pwON (0.53) and pwMS (0.94). In pwNON, but not pwON, higher sNFL z scores were associated with an elevated risk for a subsequent attack (pwNON: HR 1.63 [95% CI 1.12 to 2.27], p = 0.005; pwON: HR 0.80 [95% CI 0.51-2.27], p = 0.318) and new MRI T2 lesions (pwNON: HR 1.66 [95% CI 1.31 to 2.11], p < 0.001; pwON: HR 1.16 [95% CI 0.82 to 1.63], p = 0.404). sGFAP z scores were associated with a lower risk of a subsequent attack in pwON (HR 0.34 [95% CI 0.12 to 0.98], p = 0.047). Conclusion sNFL but not sGFAP predicted future clinical and MRI disease activity only in pwNON, potentially suggesting that the prognostic value of sNFL may depend on the type of the first manifestation.
Zuerst veröffentlicht: 12. November 2025
Gesehen am 12.02.2026